1985
DOI: 10.1055/s-2007-1014145
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Vancomycin versus Placebo in Arterial Prosthetic Reconstructions

Abstract: Vascular reconstructive surgery with the placement of prosthetic material caudal to the diaphragm is occasionally associated with postoperative wound infection. These infections often lead to amputation and can be lethal. Only a few published reports contain information on the value of prophylactic antibiotic treatment with these operations, but its use is common throughout the world. To investigate this problem, a prospective, double blind, randomized study of vancomycin versus placebo in 128 vascular graft o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…While most surgeons use cephalosporins, the increasing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci as surgical wound pathogens in many institutions (34, 38) has prompted a search for alternative prophylactic regimens. Although vancomycin use in neurologic, cardiothoracic, and vascular surgery (5,16,18,19,29,41,44) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While most surgeons use cephalosporins, the increasing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci as surgical wound pathogens in many institutions (34, 38) has prompted a search for alternative prophylactic regimens. Although vancomycin use in neurologic, cardiothoracic, and vascular surgery (5,16,18,19,29,41,44) …”
mentioning
confidence: 99%
“…While most surgeons use cephalosporins, the increasing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci as surgical wound pathogens in many institutions (34,38) has prompted a search for alternative prophylactic regimens. Although vancomycin use in neurologic, cardiothoracic, and vascular surgery (5,16,18,19,29,41,44) has been evaluated, its tendency to cause hypotension (33,35) has been problematic in surgical trials. This side effect may be especially dangerous for patients already rendered hypotensive by surgical anesthesia, their underlying disease, or the need for cardiopulmonary bypass.…”
mentioning
confidence: 99%
“…Randomised double-blind placebo-controlled trials, conducted over 20 years ago (and so predating the rise of MRSA), demonstrated that antibacterial prophylaxis, administered intravenously around 1 hour pre-operatively and continued for up to 24 hours after the operation, reduced the incidence of wound infection following reconstructive arterial surgery, typically by around two-thirds 2024. The incidence of wound infection was around 7-25% with placebo, compared with around 1-6% in patients given prophylaxis (e.g.…”
Section: Antibacterial Prophylaxismentioning
confidence: 99%
“…3 All the studies analyzed in this review included both prosthetic surgery and vein graft surgery. [4][5][6][7][8][9][10][11][12][13] Surgical site infection (SSI) after arterial reconstructive surgery of the lower extremity is assumed to be a multifactorial entity. [14][15][16] Different factors appear to influence the incidence of SSI.…”
Section: Introductionmentioning
confidence: 99%